The Role of Nahdlatul Ulama in the Transmission of Hadith in Indonesia: Literature Analysis and Scientific Contributions - Ilmi, Riyadhotul; Siregar, Idris; Dewi, Nabila Syahlita; Riadi, Annisa Khumairoh; Siregar, Miktahul Hasanah; Siregar, M. Ramadhan; Rabbani, M. Yaffi (Global Education Journal, 2026)
This research aims to examine the role of Nahdlatul Ulama (NU) in the process of transmitting hadith in Indonesia and its contribution in maintaining the sustainability of Islamic science. This research is based on the importance of understanding how hadith is not only transmitted as a text, but also as a practice of life in society through the role of scholars. This research applies the library research method by trying to review relevant literature to be used as a source of information, both in the form of books, journals, hadith books, and other scientific sources related to the NU scientific tradition and hadith studies. The results of the study show that the transmission of hadith in the NU tradition has a distinctive character, namely based on scientific sanad, oriented to Islamic boarding schools, mediated by kiai, and integrated with the social life of the community. This pattern emphasizes not only the textual aspect, but also the contextual and practical dimension of the hadith. Thus, hadith is maintained in its authority as well as relevant in people's lives. This transmission contributes to grounding moderate, adaptive, and sustainable Islamic teachings in Indonesia.